Numerical simulation of energy cascade in turbulent fluids - Rodriguez Carranza, Alexis (2022)
Transfer of energy from large to small scales in turbulent flows is described as a flux of energy from small wave numbers to large wave numbers in the spectral representation of the Navier-Stokes equation. The problem of resolving the relevant scales in the flow corresponds in the spectral representation to determining the spectral truncation at large wave numbers. The effective number of degrees of freedom in the flow depends on the Reynolds number and a numerical simulation of the Navier Stokes equation for high Reynolds numbers is impractical without some sort of reduction of the number of degrees of freedom. The shell models are constructed to obey the same conservation laws and symmetries as the Navier Stokes equation as an alternative. In this work we present the Sabra shell model for the study of the energy cascade of turbulence and we will show numerically that the energy dissipation is approximately -1/3 which is in agreement with the theory K41.